Lambda phage genetic switch as a system with critical behaviour - Vohradsky, Jiri (Journal of theoretical biology, 2017)
Critical behaviour pervades scientific disciplines as diverse as geology, economy or sociology. The critical behaviour of cell control systems is an open issue whose role has not yet been fully explored. The control of the expression of lambda phage DNA in the host cell can be classified as a system with critical behaviour. Lambda phage is a virus that infects Escherichia coli. Its core genes maintain one of two states; lysogeny or lysis. Current knowledge of the lambda phage genetic network allows to build a computational model of transcriptional control of the genes involved in the lytic-lysogenic switch and to simulate the temporal changes of their expression. Here, we focused on the computational simulation of these gene expressions to demonstrate critical behaviour of the system.
Keywords: modely genetické; lyzogenie; Gene Regulatory Networks; virové geny; genové regulační sítě; zvířata; Gene Expression Regulation, Viral; bakteriofág lambda; Lysogeny; Animals; Genes, Viral; regulace exprese virových genů; Escherichia coli; Bacteriophage lambda; Models, Genetic